Description of The Level Of Knowledge Dietary Patterns for Diabetes Mellitus Among The Elderly at The Brati Community Health Center - Charisma Alzura; Adisty Rose Artistin (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
As per the data from World Population Projection, there are currently 901 million individuals who are over 60 years of age. It is anticipated that this number will rise by approximately 56%, from 901 million to 1.4 billion. Hyperglycemia, or elevated blood sugar levels, is a hallmark of diabetes mellitus (DM), a chronic metabolic disease brought on by an imbalance between the supply and demand of insulin (David et al., 2018). Under the heading "Overview of the Knowledge Level of the Elderly About the Diabetes Mellitus Diet at the Brati Community Health Center," the author expresses interest in studying the lack of knowledge that the elderly have regarding the diabetes mellitus diet..The purpose of the study is to find out how much the elderly at the Brati Community Health Center know about the diabetes mellitus diet in 2024. This kind of cross-sectional, quantitative research uses an analytical correlation design. 71 respondents in all were used for the sample selection process in this study, which used total sampling. Cross-tabulation analysis was used to examine the research data, which were collected via a questionnaire about knowledge of the Diabetes Mellitus diet (crosstab). The majority of respondents, or 56 persons (78.9%), had a good understanding of the Diabetes Mellitus Diet, according to the results of a univariate analysis of the respondents' characteristics and their level of diet knowledge. According to the cross-tabulation results, women in their 60s and 70s with upper secondary education, a 3- to 5-year illness duration, and normal GDS measurement results <126 mg/dL were identified as having a good level of knowledge about the DM diet. Keywords: Diabetes Mellitus, Elderly, Level of Knowledge